(3eLeY GdCMHGH hJPcQI Chdi GdCdHGHs - (3CHh YHO Gddg eMeO Hf GdMSf Hf YHO Gddg GdMSfj GdhGSWi GdTGaYjs; (3CHh fYje,J (B430 (3g` s ((3eMeO Hf YKeGf GdSdei s)
(3ChdgG (B:s
(3hHYO aEfG PGcQhf ai gPG GdcJGH JQGLe QLGd JTQaJ Hge GdOfjG dNUJ Pdc ef cJGH MdjI GdChdjGA ddMGaX CHj fYje hVeeJ Edi Pdc cdGe CHj GdaQL GHf GdLhRi ai UahJg s
(3BNQgG (B:s
(3hfNJe GdcJGH HeG HOCfG Hg ChdkG hgh MeO Gddg YOO Yahg Yf Ndbg Pi GdLdGd hGdEcQGe hhdi GdWhd hGdEfYGe (B,(3MSHfG Gddg hfYe Gdhcjd hdG Mhd hdGbhI GdG HGddg GdYdi GdYXje s
(3GfXQ Qbe (B" 778" (3JGQjNs
(3Chdg agQSJ HCSeGA GdeJQLejfs
(3hgh JQGLe ai CYjGf GdUhajIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs